2022
DOI: 10.1371/journal.pone.0261675
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol induced hepatic retinoid depletion is associated with the induction of multiple retinoid catabolizing cytochrome P450 enzymes

Abstract: Chronic alcohol consumption leads to a spectrum of liver disease that is associated with significant global mortality and morbidity. Alcohol is known to deplete hepatic vitamin A content, which has been linked to the pathogenesis of alcoholic liver disease. It has been suggested that induction of Cytochrome P450 2E1 (CYP2E1) contributes to alcohol-induced hepatic vitamin A depletion, but the possible contributions of other retinoid-catabolizing CYPs have not been well studied. The main objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…The Ferdouse et al study [ 146 ] did show, in agreement with a recent RNA-sequencing study of livers from alcohol-treated mice by Melis et al [ 147 ], that 3–4 weeks of chronic alcohol treatment leads to robust and broad hepatic mRNA increases in numerous CYPs (including Cyp2c29, Cyp3a11, Cyp26a1, and Cyp26b1) that are capable of degrading retinoids [ 125 ]. These data strongly suggest that in addition to CYP2E1, alcohol-induced CYP450s, including the RA hydroxylases CYP26A1 and CYP26B1, are likely involved in alcohol-mediated reductions in hepatic retinoids.…”
Section: The Roles Of Retinoids In the Pathogenesis And Treatment Of ...supporting
confidence: 64%
See 4 more Smart Citations
“…The Ferdouse et al study [ 146 ] did show, in agreement with a recent RNA-sequencing study of livers from alcohol-treated mice by Melis et al [ 147 ], that 3–4 weeks of chronic alcohol treatment leads to robust and broad hepatic mRNA increases in numerous CYPs (including Cyp2c29, Cyp3a11, Cyp26a1, and Cyp26b1) that are capable of degrading retinoids [ 125 ]. These data strongly suggest that in addition to CYP2E1, alcohol-induced CYP450s, including the RA hydroxylases CYP26A1 and CYP26B1, are likely involved in alcohol-mediated reductions in hepatic retinoids.…”
Section: The Roles Of Retinoids In the Pathogenesis And Treatment Of ...supporting
confidence: 64%
“…Nevertheless, the conclusions from these studies were in agreement that alcohol promotes hepatic RA catabolism [ 133 , 146 , 147 ]. However, this phenomenon does not appear to occur in some extra-hepatic tissues, as Kane et al [ 133 ] also demonstrated that chronic alcohol exposure increases RA levels in the testes, and, consistent with another report [ 149 ], the brain.…”
Section: The Roles Of Retinoids In the Pathogenesis And Treatment Of ...mentioning
confidence: 60%
See 3 more Smart Citations